2016
DOI: 10.3389/fnhum.2016.00061
|View full text |Cite
|
Sign up to set email alerts
|

Bicycling and Walking are Associated with Different Cortical Oscillatory Dynamics

Abstract: Although bicycling and walking involve similar complex coordinated movements, surprisingly Parkinson’s patients with freezing of gait typically remain able to bicycle despite severe difficulties in walking. This observation suggests functional differences in the motor networks subserving bicycling and walking. However, a direct comparison of brain activity related to bicycling and walking has never been performed, neither in healthy participants nor in patients. Such a comparison could potentially help elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 71 publications
16
70
0
Order By: Relevance
“…Indeed, we observed a cyclical increase in EEG-EMG coherence that approximately coincided with the co-contraction of two leg muscles. Such a pattern is similar to the cyclical increase in coherence that occurs during treadmill walking (Petersen et al, 2012) as well as the cyclical increase in the activity of the sensorimotor cortex during robot-assisted walking (Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016), pedaling on a stationary bike (Storzer et al, 2016), and rhythmic finger movements (Seeber et al, 2016). …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Indeed, we observed a cyclical increase in EEG-EMG coherence that approximately coincided with the co-contraction of two leg muscles. Such a pattern is similar to the cyclical increase in coherence that occurs during treadmill walking (Petersen et al, 2012) as well as the cyclical increase in the activity of the sensorimotor cortex during robot-assisted walking (Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016), pedaling on a stationary bike (Storzer et al, 2016), and rhythmic finger movements (Seeber et al, 2016). …”
Section: Discussionsupporting
confidence: 59%
“…However, recent functional neuroimaging studies in humans have shown that the midline (i.e., the most medial) primary sensorimotor cortex is significantly active during steady-state walking (Fukuyama et al, 1997; Hanakawa et al, 1999; Miyai et al, 2001; Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016). Specifically, within the gait cycle, the midline primary sensorimotor cortex cyclically increases its activity approximately between mid-beta and low-gamma frequencies (Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016). Furthermore, Petersen et al (2012) have reported that, during treadmill walking, the activities of the midline primary motor cortex and the foot dorsiflexor become cyclically coherent, with similar timing and frequency range as the aforementioned increase in the midline sensorimotor activity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, modulation of cortical oscillatory activity in the beta band during transitions between rest and pedaling conditions was observed (Storzer et al, 2016). Similarly, Wagner et al (2012) and Seeber et al (2014) showed a beta band decrease during walking compared to rest.…”
Section: Methodsmentioning
confidence: 82%
“…Recently, it has been shown using scalp EEG that bicycling relative to walking has a stronger sustained cortical activation and less demanding cortical motor control within the movement cycle (Storzer et al, 2016). This is probably due to the fact that walking demands more phase-dependent sensory processing and motor planning, because each leg is independent in altering stance and swing movement phases.…”
Section: Introductionmentioning
confidence: 99%
“…; Storzer et al. ; Winslow et al. ), 2) greatly reduced following lesion of the corticospinal tract (Hansen et al.…”
Section: Discussionmentioning
confidence: 99%